2020
DOI: 10.3389/fpsyg.2020.01600
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Acoustic Environment in Hospital Wards on Patient Physiological and Psychological Indices

Abstract: Patients in general wards are often exposed to excessive levels of noise and activity, and high levels of noise have been associated with depression and anxiety. Previous studies have found that an appropriate acoustic environment is beneficial to the patient's therapeutic and treatment process; however, the soundscape is rarely intentionally designed or operated to improve patient recovery, especially for psychological rehabilitation. To gain the most accurate, and least variable, estimate of acoustic environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
0
17
0
1
Order By: Relevance
“…The 1-min equivalent sound pressure level (SPL) was adjusted to 55 dB(A) for each audio frequency by AuditionCS6 to remove differences in volume during the stimulation of the four sounds and to ensure that the participants listened to the four auditory stimulus sounds under similar playback SPL conditions. The background noise was below 45 dB(A) during the survey (Zhou et al, 2020 ). The selected retirement facilities met the following two criteria: (1) providing sufficient daily activities and being fully equipped to ensure that the conditions in which older adults reside would not affect their evaluation of the sound sources and (2) having 10 or more residents, allowing efficient distribution of the questionnaire and increasing the statistical reliability of collected data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1-min equivalent sound pressure level (SPL) was adjusted to 55 dB(A) for each audio frequency by AuditionCS6 to remove differences in volume during the stimulation of the four sounds and to ensure that the participants listened to the four auditory stimulus sounds under similar playback SPL conditions. The background noise was below 45 dB(A) during the survey (Zhou et al, 2020 ). The selected retirement facilities met the following two criteria: (1) providing sufficient daily activities and being fully equipped to ensure that the conditions in which older adults reside would not affect their evaluation of the sound sources and (2) having 10 or more residents, allowing efficient distribution of the questionnaire and increasing the statistical reliability of collected data.…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies have proved that the following six types of sound sources may help to improve mood, namely, music, birdsong, fountain, stream, wind/rain, and wind/leaves (Zhongzhe, 2016;Hong et al, 2020). Birdsong was mainly concentrated in the high-frequency region and other sound sources are mainly concentrated in low frequencies, while the sound of the music had an obvious rhythm.…”
Section: Sound Sourcementioning
confidence: 99%
“…The physical elements and design of service space guide the user experience, define their activities, and stimulate active interaction with users and between users through various touchpoints (Chronis, 2019). Prior research in multiple disciplines, including environmental psychology, organizational behavior, marketing, and medicine, has examined the influence of healthcare servicescapes and environment design on the users' cognition (Schreuder et al, 2016;Suess and Mody, 2018), emotion (Hamed et al, 2019;Quan et al, 2016), physiology (Zhou et al, 2020) and social interaction (Karp et al, 2019;Lacanna et al, 2019). This stream of research has shown that the environment can influence its users' behavior.…”
Section: User-centered Theorymentioning
confidence: 99%
“…, 2016) in the context of pediatric care. In terms of the auditory environment, hospital noise was found to affect patients' sleep (Antonio, 2020) and impede the recovery process (Iyendo, 2017), while music plays an important role in physiological stress recovery (Zhou et al. , 2020).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Most studies of background noise in hospitals (3)(4)(5)(6) have concentrated on patient impacts (sleep patterns, wellbeing and satisfaction) rather than impact on staff communication. A large variety of methods of measurement have been used, which makes comparison of results difficult (7).…”
Section: Introductionmentioning
confidence: 99%